W poszukiwaniu dojrzałej tożsamości: kim są kobiety i mężczyźni 50+ we współczesnym społeczeństwie polskim? = In quest of mature identity: who are women and men 50+ in modern Polish society - Trzop, Beata (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The aim of this article is to identify and characterize, from the perspective of sociological research, the elements of identity of mature women and men in the stage of life between middle and late adulthood. Data analyzed in the article comes from two research projects: "Mature women - selected aspects of life": research carried out in 2012, and "Mature men in modern Polish society - selected aspects of life": research carried out in 2014 and 2015.
Keywords: femininity; masculinity; identity; senility; social roles; kobiecość; męskość; tożsamość; starość; role społeczne